International peace academy - Peacekeeper's Handbook (New York, 1984)
Peacekeeper's Handbook is a ready reference for the planning and conduct of peacekeeping operations, both within the framework of the United Nations and in a regional or multinational setting. Topics covered include standing operating procedures, operational handling and techniques, logistics, and communications, along with preparation and preparedness and the role of civilian police in peacekeeping operations. Planning and procedures for medical services for international peacekeeping operations are also considered. This guidebook is comprised of 14 chapters and begins with an overview of the theoretical concept of international peacekeeping, followed by a discussion on the main organs of the United Nations, their functions in relation to international peace and security, and their powers and their responsibilities. The following chapters focus on the principles on which the policy on UN peacekeeping is based; the skill and technique requirements for the chief aspects of a peacekeeper's duties; and the organization and procedures for the logistics support of a UN operation at the level of UN Headquarters, Force Headquarters, and National Contingent. The organization and structure of the communications system within a UN Force are then described, along with the organization and procedure employed by the UN and its Forces/Missions to facilitate good public relations and an effective press information service. This text concludes by outlining the main principles and procedures in establishing a medical service. This handbook will be a valuable resource for diplomats, military officers, policymakers, academicians, students, and those interested in dispute settlement and conflict management.
Keywords: United Nations armed forces handbooks